2015
DOI: 10.1371/journal.ppat.1004663
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Plays a Functional Role in Helicobacter pylori-induced Epithelial Cell Proliferation

Abstract: The cytotoxin-associated gene (Cag) pathogenicity island is a strain-specific constituent of Helicobacter pylori (H. pylori) that augments cancer risk. CagA translocates into the cytoplasm where it stimulates cell signaling through the interaction with tyrosine kinase c-Met receptor, leading cellular proliferation. Identified as a potential gastric stem cell marker, cluster-of-differentiation (CD) CD44 also acts as a co-receptor for c-Met, but whether it plays a functional role in H. pylori-induced epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 49 publications
4
142
1
2
Order By: Relevance
“…After PMSS1 infection, CD44 was expressed at the base of the corpus glands (Fig. 4A, bottom), and there was a significant increase in CD44 expression compared with that in control mice, as reported in previous studies (P Ͻ 0.05) (36,37) (Fig. 4B and C).…”
Section: Sox9 Expression In Gastritis Induced By H Pylorisupporting
confidence: 86%
See 1 more Smart Citation
“…After PMSS1 infection, CD44 was expressed at the base of the corpus glands (Fig. 4A, bottom), and there was a significant increase in CD44 expression compared with that in control mice, as reported in previous studies (P Ͻ 0.05) (36,37) (Fig. 4B and C).…”
Section: Sox9 Expression In Gastritis Induced By H Pylorisupporting
confidence: 86%
“…Another stem cell marker, CD44, was recently reported to play a functional role in H. pylori-induced epithelial cell proliferation and metaplasia (21,36). Khurana et al showed that CD44 expression was found in the isthmus in control mice, which expanded to the base after H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cell line models, CagA binds to the host c-MET receptor and promotes a motogenic response (Churin et al, 2003). In gastric organoids, CagA also binds to c-Met and likely as a response, host cell proliferation is induced in a CagA-dependent manner (Bertaux-Skeirik et al, 2015;McCracken et al, 2014). Together, these studies establish organoids as a model for H. pylori infection by demonstrating that organoids reproduce important hallmarks of the infection.…”
Section: Gastric Organoids and Helicobacter Pylorimentioning
confidence: 79%
“…Injected bacteria can adhere to the epithelium and target apical cell-cell junctions Wroblewski et al, 2010). The bacteria are viable, as shown by re-culturing of H. pylori from organoids Bertaux-Skeirik et al, 2015) and even expand inside the organoids, suggesting that organoids may provide essential niche factors (Bertaux-Skeirik et al, 2015). Epithelial cells in organoids secrete urea, which induces a chemotactic response in the bacteria and may contribute to the establishment of a replicative niche in the organoids .…”
Section: Gastric Organoids and Helicobacter Pylorimentioning
confidence: 99%
“…Gastrointestinal organoids have also proven useful in investigating other diseases that are difficult to study in animal models. Intestinal organoids infected with Clostridium difficile (Leslie et al, 2015) or gastric organoids infected with Helicobacter pylori (Bertaux-Skeirik et al, 2015;McCracken et al, 2014) have been essential in understanding some of the earliest processes in the epithelial response to pathogens. Additionally, with the advent of CRISPR/Cas9 gene editing, disease modeling, mutation correction and personalized medicine are now possible in patient-specific iPSC-derived organoids (Hockemeyer and Jaenisch, 2016).…”
Section: Interactions Between Multiple Germ Layers Improve In Vitro Cmentioning
confidence: 99%